Leveraging genotype × management synergies to enhance pigeonpea productivity, profitability, and sustainability in semi-arid tropics - Sawargaonkar, Gajanan L.; Kamdi, Prasad J.; Kale, Santosh; Shinde, Santosh; Das, Susree Snigdha; Kausadikar, Harihar; Singh, Ramesh; Jat, M. L. (Frontiers in Agronomy, 2025)
IntroductionPigeonpea (Cajanus cajan L.) is a vital legume crop in semi-arid tropics with high yield potential and adaptability. However, its productivity is limited by poor adoption of climate-resilient technologies and inappropriate genotype selection, especially under climate variability.MethodsA two-year field experiment (2013–14 and 2014–15) was conducted at ICRISAT, India, to evaluate the impact of seedling age (14 to 49 days) and genotype (ICPH2740, Maruti, TS3R) on pigeonpea performance under direct seeding and transplanting methods. The experiment followed a factorial randomized block design. Key parameters studied included yield, water productivity, economic returns, and soil carbon dynamics.ResultsTransplanting 21-day-old seedlings significantly enhanced grain yield (2536 and 2430 kg ha⁻¹), water productivity, and benefit-cost ratio compared to direct seeding and other transplanting ages. ICPH2740 outperformed other genotypes in grain yield, economic water productivity, and soil carbon sequestration. The highest carbon build-up rate (0.65 Mg ha⁻¹ yr⁻¹) was observed in ICPH2740 at 21 DAS transplanting.DiscussionThe findings highlight the superiority of transplanting medium-duration genotypes (especially ICPH2740) at 21–35 DAS over direct seeding in improving productivity, profitability, and sustainability. This strategy is demonstrated as a climate-resilient practice for rainfed pigeonpea cultivation in semi-arid tropics.